O estereótipo na comunicação : uma análise em documentários sobre terrorismo islâmico - Espindola, Polianne Merie (2013)
This research aims to analyze whether objects chosen address stereotypical visions on issues related to Islamic terrorism in the eastern and western perspective. Two documentaries were chosen as objects, they are: Control Room and Obsession: Radical Islam's War Against The West . For that will be used to phenomenology, a research aimed at reconstructing the perspective of the individual to the social reality in which they live and that is also composed and modified by this individual. In this approach the phenomena can be reflected from a frameworks to, a look, the personal appropriation of environments, objects and practices. The principal authors, however not unique theoretical matrix that underlie this research are: Alfred Schutz's phenomenological sociology; Joao Carlos Correia, contemporary author who uses the concepts of Alfred Schutz theoretical contribution to communication and Walter Lippman. The expected results are check, according to the categories used to analyze the documentaries, they reinforce stereotypes about thematic linked to Islamic terrorism, even with the possibility of individuals to access information about the various contents on the internet today.